A comparison of upper body power, strength, endurance and flexibility characteristics of sport climbers and boulderers - Leong, C. H. (California State University, 2009)
This causal comparative study compared the upper body performance characteristics (UBPC) of sport climbers and boulderers, and investigated the relationship between the UBPC and climbing skill levels for the two groups. Twenty-four sport climbers (12 males, 12 females) and 21 boulderers (11 males, 10 females), with a wide range of climbing skill volunteered as participants. Shoulder flexibility, Wingate anaerobic power, push-up power, maximal campusboard reach, handgrip and pinchgrip strength, estimated 1-RM lat pulldown strength, pull-up endurance, push-up endurance and anthropometry were measured. No significant anthropometric and UBPC differences were found between male sport climbers and boulderers. Female boulderers had significantly greater handgrip and pinchgrip strength than female sport climbers (p < 0.05). Maximal campusboard reach was significantly related to climbing skill level for all groups (p < 0.05). Therefore, grip strength may be more important for female boulderers than female sport climbers, and campusboard training may improve one's climbing ability.